2023
DOI: 10.1007/s11219-023-09629-1
|View full text |Cite
|
Sign up to set email alerts
|

Just-in-time defect prediction for mobile applications: using shallow or deep learning?

Abstract: Just-in-time defect prediction (JITDP) research is increasingly focused on program changes instead of complete program modules within the context of continuous integration and continuous testing paradigm. Traditional machine learning-based defect prediction models have been built since the early 2000s, and recently, deep learning-based models have been designed and implemented. While deep learning (DL) algorithms can provide state-of-the-art performance in many application domains, they should be carefully sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Commonly used standalone classifiers include Logistic Regression [3,23,24], Naïve bayes [25], Support Vector Machine [26], Decision Tree [27], and Neural Network [28]. Whereas for ensemblebased learners range from single ensemble learner such as Random Forest [29] to multi-layer ensembles [27,30,31]. Prior JIT-SDP has utilized machine learning with batch learning to formulate such prediction models.…”
Section: A Modelling Of Software Defect Predictionmentioning
confidence: 99%
“…Commonly used standalone classifiers include Logistic Regression [3,23,24], Naïve bayes [25], Support Vector Machine [26], Decision Tree [27], and Neural Network [28]. Whereas for ensemblebased learners range from single ensemble learner such as Random Forest [29] to multi-layer ensembles [27,30,31]. Prior JIT-SDP has utilized machine learning with batch learning to formulate such prediction models.…”
Section: A Modelling Of Software Defect Predictionmentioning
confidence: 99%
“…Huang, QG [5] and others proposed the MTL-DNN method based on multi-task learning to address the issue of insufficient labeled training data in both the source and target projects. Additionally, research by Raymon [6] suggested that, when comparing machine learning and deep learning on mobile platforms, machine learning exhibits better predictive performance. Zhu et al [7] .…”
Section: Related Workmentioning
confidence: 99%
“…With this type of design, mean absolute error rate was found to be comparatively less. Yet another deep learning based prediction method was proposed in [7] to focus on the accuracy and time aspect. Since recently deep learning techniques have achieved significant results in several areas of applications, there is a requirement to apply for all type of problems, i.e., software defect prediction.…”
Section: Introductionmentioning
confidence: 99%